Effects of age and bamboo portion on the ash and silica content of Buluh Semantan (Gigantochloa Scortechinil) / Jamaludin Kasim and Nor Asikir Mamat - Kasim, Jamaludin; Mamat, Nor Asikir (Universiti Teknologi MARA Cawangan Pahang, 2008)
Sixty bamboo culms were harvested from six bamboo clumps and were cut into three portions namely; basal, middle and top portions. Bamboo samples were then granulated into wood meal and those retained on the 60 BS mesh sieve were used in the study to determine the ash and silica content. Age was found to significantly affect the ash and silica content. However, bamboo portion showed no significant effect.